Without using calculator, solve the following quadratic equation and put the solutions as their sum.
x 2 − 1 9 4 5 x + 7 7 6 4 = 0
Bonus : Did you notice any special relationship between them?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thanks you, that looks nicer
Null factor law
x 2 − 1 9 4 5 x + 7 7 6 4 = 0 x 2 − 1 9 4 1 x − 4 x + 7 7 6 4 = 0 x ( x − 1 9 4 1 ) − 4 ( x − 1 9 4 1 ) = 0 ( x − 4 ) ( x − 1 9 4 1 ) = 0 x = 4 o r x = 1 9 4 1
Therefore, the answer would be 4 + 1 9 4 1 = 1 9 4 5
I believe there is a shorter way do this...
Log in to reply
Do you mean to use Δ = b 2 − 4 a c ?
Log in to reply
In my mind more like...
( x 1 + x 2 ) = a − b
My math teacher ever told me about that, So since you only need to find the sum of the solutions... I'm not a good speaker tho :/
Log in to reply
@Tawaf Nasution – Oh, that's Vieta formula.
Just in case you wonder, here is it .
Problem Loading...
Note Loading...
Set Loading...
There's no need to factor the quadratic. Sum of roots can be easily obtained by vieta's formula .
Applying the formula, the sum comes as
− 1 − 1 9 4 5 = 1 9 4 5